Recreation programming : a benefits-driven approach - Kraus, Richard G. (Boston : Allyn and Bacon, 1997)
Recreation Programming: the social Context; The programming Process; Establishing Program Goaals and Objectives; Analyzing Program Participants: Demographic Factors; Recreation Program Elements: Activities and Services; Recreation Leadership and Facilities Planning...
Keywords: Leisure industry; Recreation leadership; Recreation management; Recreation -- Planning; Recreation leadership; Recreation -- Management; Leisure industry -- Management